Traditional Human Cultural Influences on Animals - Wu, Kefei (Transactions on Environment, Energy and Earth Sciences, 2024)
Many of the world’s animals are being positively or negatively affected by human production and activities in various ways of behavior and lifestyle. This paper focuses on the exploration of the many aspects of the impact of traditional human culture on animals. The results of this paper show that animals are mostly negatively affected by human traditional culture. However, efforts are being made to save and take remedial measures, this is only because the historical legacy cannot be cured in a short period of time and people need to put more efforts to improve the various conservation measures. The purpose of this study is to hope that people can remedy their negative impacts on animals in nature and to make people understand how they can do so in time. By studying various cases and collecting data from different regions, this paper aims to reveal the specific ways in which traditional practices harm wildlife. Ultimately, the call is to create a balanced, symbiotic environment where traditional practices can coexist with modern conservation efforts.